A comparative evaluation of implant stability and crestal bone loss in T-PRF-treated and conventional implants: A split-mouth clinical study - Anuraga Tejaswi Thotimpuri; Mohan Kumar Pasupuleti; Gautami Subhadra Penmetsa; Satyanarayana Raju Manthena; Naga Venkata Satya Sruthima Gottumukkala; Konathala Santosh Venkata Ramesh (Journal of Advanced Periodontology & Implant Dentistry, 2026)
Introduction: This study aimed to compare implant stability and crestal bone loss between titanium platelet-rich fibrin (T-PRF)-treated implants and conventional implants. Methods: A prospective, randomized, split-mouth clinical trial was conducted in 10 healthy patients, with 20 implants per mouth (test and control). Each patient received one T-PRF-treated implant and one conventional implant. Implant stability was assessed using implant stability quotient (ISQ) at placement and at 3 months. Crestal bone loss was evaluated radiographically at 3 and 6 months. Soft tissue parameters were assessed at follow-up visits. Results: The T-PRF group showed higher ISQ values and reduced bone loss, with trends favoring the intervention at the three-month follow-up compared with the control group. Bone loss at three and six months was lower around anterior implants in the T-PRF group than in the control group. At this time, T-PRF may help improve soft tissue measurements; however, the measured values did not differ significantly from those of the control groups. Due to limitations such as a small sample size, a relatively short follow-up period, and varying baseline crestal bone levels, these findings should be interpreted with caution. Conclusion: Due to the restrictions of this split-mouth study, T-PRF-treated sites showed a trend towards increased early implant stability and decreased crestal bone loss compared to control sites. However, because of the small sample size and short follow-up period, conclusive evidence cannot be drawn about the clinical superiority of T-PRF. Further appropriately powered randomized controlled trials with prolonged follow-up periods are necessary to determine the long-term clinical efficacy of T-PRF in implant therapy. Clinical Trial Registration number: CTRI/2022/11/047159.